2021
DOI: 10.3390/lubricants9050051
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Influence of Textured Surfaces and Lubrication Conditions on the Tribological Performance between the Compression Ring and Cylinder Liner

Abstract: The objective of the present investigation is to analyze the tribological performance between the union of the cylinder liner and the compression ring under the influence of surface texturing and different lubrication boundary conditions. The analysis is carried out by developing a numerical model, which involves hydrodynamic pressure, lubrication film thickness, textured surface, dynamic forces, and lubrication boundary conditions (starved lubrication and fully flooded lubrication). MATLAB® software (The Math… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…It is also necessary to mention that, there is a limit to the action depth threshold for the supplementary effect of micro-bearings on grease. This does not make the pit very visible and leads to a decrease in the dynamic pressure lubrication performance of surface lubrication film [28].…”
Section: Effect Of Different Surface Treatments On Aluminum Alloy Sur...mentioning
confidence: 99%
“…It is also necessary to mention that, there is a limit to the action depth threshold for the supplementary effect of micro-bearings on grease. This does not make the pit very visible and leads to a decrease in the dynamic pressure lubrication performance of surface lubrication film [28].…”
Section: Effect Of Different Surface Treatments On Aluminum Alloy Sur...mentioning
confidence: 99%
“…Garcia et al [ 147 ] in modeling analyzed also hydrodynamic lubrication and contact between asperities. They found that surface texturing of the liner led to a reduction in the asperity contact force of 20%, a total friction force of 5%, and an increase in minimum oil film thickness of 4%, so the power loss can be reduced.…”
Section: Functional Performance Of Textured Cylinder Liner Surfacesmentioning
confidence: 99%
“…They observed crossed-hatch angle as a crucial parameter and significant reduction in friction coefficient has been observed. Garcia et al 23 showed and experimentally verified that by surface texturing 25% and 5% reduction in asperity contact force and total friction force can be achieved. Xiuyi et al 24 proposed an improved contact model for analysis of tribological performance of PRCLC from the perspective of Stribeck curve.…”
Section: Introductionmentioning
confidence: 97%